Honduras : First Reviews Under the Stand-By Arrangement and Standby Credit Facility-Press Release; Staff Report; Informational Annex; Staff Supplement; and Statement by the Executive Director for Honduras. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Honduras' First Reviews Under the Stand-by Arrangement (SBA) and Standby Credit Facility (SCF). Program implementation for the first reviews has been strong. All 2014 performance criteria and indicative targets were met, most with significant margins. The authorities have also created fiscal space within the program to increase social spending and support efforts to reduce poverty. On the structural side, December 2014 and March 2015 benchmarks were also generally observed. The revised program proposed for 2015 envisages further strengthening fiscal and net international reserves targets. The IMF staff supports the completion of the first reviews under the SBA and the SCF Arrangements.